RETRACTION NOTICE TO: Model Penyelesaian Tindak Pidana Penebangan Hutan Mangrove Melalui Hukum Adat di Kecamatan Mandah Kabupaten Indragiri Hilir Provinsi Riau - Okta Zeruya Samdra Pandapotan Nainggolan (Jurnal Hukum Lex Generalis, 2022)
The manuscript entitled "Model for Solving Mangrove Forest Logging Through Customary Law in Mandah District of Indragiri Hilir Regency of Riau Province" published in Lex Generalis Law Journal Vol.2 No.11 (November 2021) on the link https://ojs.rewangrencang.com/index.php/JHLG/article/view/75 to the Editor's search has the main similarity substance with the manuscript that has been published previously in another journal, namely Riau Law Journal Vol.4 No.2 (2020) on the https://rlj.ejournal.unri.ac.id/index.php/RLJ/article/view/7856. At first glance through the title and abstract of the journal, it does not look similar between the two manuscripts. Similarly, at the time this manuscript was submitted, the editor did not find other manuscripts that bore a resemblance to this manuscript (maybe the manuscript in the RLJ journal has not been published so it cannot be detected on the searcher gunpowder). However, after seeing the discussion, especially the results of research, there are very similar equations after being compared side by side. So based on this, the Editor suspects that there is a violation of publication ethics even though some journals have been modified so that at first glance it is not similar if skimming is done. Based on these findings, the Editor attempts to contact the author of the correspondence in question (Author 3) for confirmation and clarification. Author 3 himself is a student of another author who is listed as Author 1 and Author 2 in this manuscript. According to the explanation, Author 3 did conduct research under the supervision of Author 1 and Author 2 as a guide. However, after the study is completed, Author 1 and Author 2 without the knowledge and consent of Author 3, submit the results of the study to the RLJ. Then at the same time, Author 1 and Author 2 also asked Author 3 to process the results of the study so that the visible eye did not see any difference with the manuscript sent to the RLJ. The manuscript on the RLJ takes the object of the utilization of natural resources in general. While the objects that entered us are focused on mangrove forests. However, the research results of these two manuscripts are very identical. Thus, there are indications of fraud where the results of the same study are published twice (double publication) with the same legal settlement and similar research sources, or at least there is potential for copyright infringement or plagiarism. Therefore, the Editorial decided to retract this manuscript from our journal.